Job Satisfaction, Work Performance and Organizational Commitment of Academic Librarians - Eiman, Glory Jean (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the job satisfaction of academic librarians and its relationship with work performance and organizational commitment in selected Higher Education Institutions in Sultan Kudarat. Anchored on Herzberg’s Two-Factor Theory, the study investigated job satisfaction in terms of compensation, recognition, interpersonal relations, professional advancement and tenure, and job itself, and determined its influence on work performance and organizational commitment. A descriptive-correlational and comparative survey design was employed. Data were gathered using a researcher-made questionnaire adapted from Tabile (1999) and Lester (1984) and administered to 29 professional and paraprofessional librarians. Statistical analyses included frequency and percentage distribution, mean, One-Way Analysis of Variance (ANOVA), Pearson Product-Moment Correlation, and Multiple Regression Analysis. The findings revealed that most respondents were college graduates, employed in private institutions, held contractual positions, and had less than five years of service. Librarians were generally moderately satisfied with their jobs, with job itself obtaining the highest satisfaction rating, while compensation received the lowest rating. Work performance was very satisfactory in human and conceptual skills and satisfactory in technical skills. Significant differences in job satisfaction were observed based on employment status, with permanent librarians demonstrating higher satisfaction than contractual librarians. Significant positive relationships were also found between job satisfaction and work performance and between job satisfaction and organizational commitment. Regression analysis further indicated that job satisfaction explained 37% of the variation in work performance and 69% of the variation in organizational commitment. The study concluded that job satisfaction plays a significant role in enhancing employee performance and commitment. It recommends improving compensation, benefits, professional development opportunities, recognition systems, and career advancement programs to strengthen librarian satisfaction and organizational effectiveness. The study aligns with SDG 4 (Quality Education), SDG 8 (Decent Work and Economic Growth), and SDG 16 (Peace, Justice, and Strong Institutions) by promoting effective educational support services, improved workplace conditions, and stronger institutional practices. Its sustainability impact lies in supporting educational, institutional, and human resource sustainability through enhanced librarian productivity, commitment, and service quality in higher education institutions.